2022
DOI: 10.1111/jfpp.17012
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid microwave with hot air drying of black‐gram ( Vigna mungo L) nuggets: Drying characteristics, modeling, and process optimization

Abstract: Black‐gram nuggets (BGNs) were dried using combined hot air‐microwave drying (CHMD). Drying kinetics, quality characteristics, and optimization of drying parameters of BGN with the variation of microwave power densities (MPD, 1.33–2 W/g) and temperatures (T, 40–70°C) were studied. Moreover, modeling, effective moisture diffusivity, and nutritional content were also investigated. Drying rate raised initially and attained a peak, followed by a falling rate period. Midilli–Kucuk was the best‐fitted model to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Similar results were found by Musielak & Kieca (2014), they also showed that both increase in temperature and time can damage the product quality when worked with beetroot and carrot slices. Increasing the temperature and MWPD increased the effective moisture diffusivity while decreasing the firmness and drying rate of Black-gram nuggets (Sakre et al, 2022).…”
Section: Resultsmentioning
confidence: 93%
“…Similar results were found by Musielak & Kieca (2014), they also showed that both increase in temperature and time can damage the product quality when worked with beetroot and carrot slices. Increasing the temperature and MWPD increased the effective moisture diffusivity while decreasing the firmness and drying rate of Black-gram nuggets (Sakre et al, 2022).…”
Section: Resultsmentioning
confidence: 93%